O efeito do tamanho do lote de transferência no lead time em um ambiente flow shop: uma análise quantitativa - Barco, Clarissa Fullin (2016)
This thesis proposes to evaluate the effect of transfer batch size on lead time reduction in flow shop environments (balanced and unbalanced, with a bottleneck). In order to achieve this objective, Design Science was used as a research method, in which a static simulation model is proposed and several scenarios are analyzed and evaluated in relation to important Production Management theories. The model proposed to represent a flow shop uses the Factory Physics equations (HOPP; SPEARMAN, 2008) e considers the following shop-floor variables: i) the average setup time; ii) average defect rate; iii) mean time between failures; iv) mean time to repair the machine; v) variability in processing time; vi) variability of the time between arrivals of orders and vii) transfer batch size. The results demonstrate that for both balanced and unbalanced environment, transfer batch size has little effect on lead time, when operating with a process batch size away from optimal batch size (minimum point of the lead time - lot size curve proposed by Karmarkar et al. (1985)). To get a good lead time performance, it is first necessary to reduce process batch size before making efforts to reduce transfer batch. For an unbalanced environment, reducing process batch size only at the bottleneck, coupled to transfer batch size reduction across the flow shop, provided a lead time reduction on the order of 30%, while the remainder flow shop operated with large process batches. In such configuration, the contribution from setup time reduction at the bottleneck machine has generated a small effect on the lead time performance considering the parameters used in this work.